Synthesis, molecular structure and cytotoxicity of molecular materials based on water soluble half-sandwich Rh(III) and Ir(III) tetranuclear metalla-cycles - Gupta, Gajendra; Murray, Benjamin S.; Dyson, Paul J.; Therrien, Bruno (My University, 2013)
The neutral dinuclear complexes [(?5-C5Me5)2Rh2(?-dhnq)Cl2] (1) and [(?5-C5Me5)2Ir2(?-dhnq)Cl2] (2) (dhnqH2 = 5,8-dihydroxy-1,4-naphthoquinone) were obtained from the reaction of [(?5-C5Me5)M(?-Cl)Cl]2 (M = Rh, Ir) with dhnqH2 in the presence of CH3COONa. Treatment of 1 or 2 in methanol with linear ditopic ligands L (L = pyrazine, 4,4'-bipyridine or 1,2-bis(4-pyridyl)ethylene), in the presence of AgCF3SO3, affords the corresponding tetranuclear metalla-rectangles [(?5-C5Me5)4M4(?-dhnq)2(?-L)2]4+ (L = pyrazine, M = Rh, 3; M = Ir, 4; L = 4,4'-bipyridine, M = Rh, 5; M = Ir, 6; L = 1,2-bis(4-pyridyl)ethylene, M = Rh, 7; M = Ir, 8). All complexes were isolated as their triflate salts and were fully characterized by IR, 1H and 13C NMR spectroscopy, and some representative complexes by single-crystal X-ray structure anal. The X-ray structures of 3, 5 and 6 confirm the formation of the tetranuclear metalla-cycles, and suggest that complexes 5 and 6 possess a cavity of sufficient size to encapsulate small guest mols. In addn., the antiproliferative activity of the metalla-cycles 3-8 was evaluated against the human ovarian A2780 (cisplatin sensitive) and A2780cisR (cisplatin resistant) cancer cell lines and on non-tumorigenic human embryonic kidney HEK293 cells. All cationic tetranuclear metalla-rectangles were found to be highly cytotoxic, with IC50 values in the low micromolar range. [on SciFinder(R)]